The role of nucleotide opening dynamics in facilitated target search by DNA-repair proteins - Mishra, Sujeet Kumar; Sangeeta, Sangeeta; Heermann, Dieter W.; Bhattacherjee, Arnab (Biochimica et biophysica acta. Gene regulatory mechanisms, 2024)
Preserving the genomic integrity stands a fundamental necessity, primarily achieved by the DNA repair proteins through their continuous patrolling on the DNA in search of lesions. However, comprehending how even a single base-pair lesion can be swiftly and specifically recognized amidst millions of base-pair sites remains a formidable challenge. In this study, we employ extensive molecular dynamics simulations using an appropriately tuned model of both protein and DNA to probe the underlying molecular principles. Our findings reveal that the dynamics of a non-canonical base generate an entropic signal that guides the one-dimensional search of a repair protein, thereby facilitating the recognition of the lesion site. The width of the funnel perfectly aligns with the one-dimensional diffusion length of DNA-binding proteins. The generic mechanism provides a physical basis for rapid recognition and specificity of DNA damage sensing and recognition.
Gesehen am 09.09.2024